Therapeutic lifestyle strategies taught in Nigerian pharmacy schools (2022)
Background: Therapeutic lifestyle modifications are the basis of treatment and prevention of numerous chronic diseases. Objectives: To describe the therapeutic lifestyle modifications taught in Nigerian pharmacy schools. METHODS: A short self-administered online questionnaire (using Google Form), to ascertain the curricular coverage of therapeutic lifestyle modification in undergraduate pharmacy training programs was sent to the Deans of all accredited schools of pharmacy in Nigeria (n = 20). The collected data were summarized using descriptive statistics. RESULTS: Thirteen schools of pharmacy participated in the study. All the schools taught at least one of the 10 specified therapeutic lifestyle strategies. Less than a third taught smoking cessation (2.0, 15.4%), lifestyle modifications for pregnant women (2.0, 15.4%) and patients with mental health issues (1.0, 7.7%). CONCLUSIONS: There are variations in the content of teaching of therapeutic lifestyle approaches in Nigerian pharmacy schools. To enhance therapeutic lifestyles, it is essential to improve the content and teaching of therapeutic lifestyle strategies in Nigerian pharmacy schools. All schools should do more to ensure that they are providing adequate training to enable students to be prepared for delivering support to all patients (including pregnant women and mental health patients) on therapeutic lifestyles.